Magnetic response of mixed Ising ferrimagnets in the presence of external magnetic fields - Buendía, G. M.; Machado, E. (Ciencia, 1970)
In this work we are going to present a numerical study based on the Monte Carlo method of a mixed Ising ferrimagnet on a square lattice. We are particularly interested in studying the magnetic response of the system to an external field and the behavior of the compensation temperature. We found that there is a strong dependence of the compensation temperature with the field. We also notice the existence of metaestable states with very long lifetimes and compensation points at lower temperatures that the ones for the stable states.